MELAMPAUI DOMINASI MASKULINITAS HEGEMONIK MELALUI TOKOH SUPERHERO GAY DALAM NOVEL HERO KARYA PERRY MOORE - Vidiarama, Made Arya; Saktiningrum, Nur (Balai Bahasa Provinsi Jawa Timur, 2022)
Superhero is considered as an ideal figure with the image of hegemonic masculinity men. Hegemonic masculinity men are categorized as heterosexual, strong, intelligent, and dominant men. Meanwhile, homosexual men are subordinate masculinity. Perry Moore’s novel Hero presents the figure of a gay superhero. This study will explain how a gay superhero character named Thom was able to transcend the domination of hegemonic masculinity which has been synonymous with the image of a superhero. The method used is descriptive-analysis. The data taken is in the form of quotations in the novel Hero. The data that has been collected will be analyzed using the hegemonic masculinity theory popularized by R.W. Connell. The results of this study indicate that Thom is categorized as subordinate masculinity because of his sexual orientation as well as his weak, and insecure nature. As a gay superhero, Thom faces several conflicts in academics, family, and neighbourhood. However, he showed that he could change the perceptions of people. Through this novel, Perry Moore tried to dismantle superhero stereotypes.